2007
DOI: 10.1016/j.bbmt.2007.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Postgrafting Immunosuppressive Regimens on Nonrelapse Mortality and Survival after Nonmyeloablative Allogeneic Hematopoietic Stem Cell Transplant Using the Fludarabine and Low-Dose Total-Body Irradiation 200-cGy

Abstract: The development of nonmyeloablative (NM) hematopoietic cell transplantation (HCT) has extended the potential curative treatment option of allografting to patients in whom it was previously contraindicated because of advanced age or comorbidity. Acute and chronic graft versus host disease (GVHD) and its consequent nonrelapse mortality (NRM), remains the major limitation of NM HCT. In this report, we analyzed the outcome of 67 patients (median age, 45 years) with hematologic diseases receiving NM conditioning wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…7 The best outcomes with allogeneic transplantation are achieved through transplantation of hematopietic progenitor cells from an HLA-matched related or unrelated donor; however, even in this setting grades II-IV acute GVHD (aGVHD) occur in 30-50% of patients. 6,8 Further, for any degree of HLA disparity, OS generally decreases as a consequence of nonrelapse mortality from GVHD and complications arising from its management. 9,10 The use of antithymocyte globulin (ATG) as in vivo T-cell depletion for the prevention of GVHD has been studied in the unrelated donor (URD) transplant setting, primarily following myeloablative conditioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The best outcomes with allogeneic transplantation are achieved through transplantation of hematopietic progenitor cells from an HLA-matched related or unrelated donor; however, even in this setting grades II-IV acute GVHD (aGVHD) occur in 30-50% of patients. 6,8 Further, for any degree of HLA disparity, OS generally decreases as a consequence of nonrelapse mortality from GVHD and complications arising from its management. 9,10 The use of antithymocyte globulin (ATG) as in vivo T-cell depletion for the prevention of GVHD has been studied in the unrelated donor (URD) transplant setting, primarily following myeloablative conditioning.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In principle, use of a RIC reduces immediate toxicities of the transplant maneuver, but the patient remains subject to morbidity and mortality associated with GVHD. 6 The ultimate efficacy of the transplant therefore depends on successful achievement of a balance between graft versus tumor effects necessary for eradication of the malignancy and complications associated with GVHD and immune incompetence. 7 The best outcomes with allogeneic transplantation are achieved through transplantation of hematopietic progenitor cells from an HLA-matched related or unrelated donor; however, even in this setting grades II-IV acute GVHD (aGVHD) occur in 30-50% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Koh et al [34] reported that the post-grafting MTX combined with cyclosporine and MMF significantly reduced the risk of grade III-IV acute GVHD as compared with a combination of cyclosporine and MMF. Consistent with their experience, the cumulative incidence of severe acute GVHD after our triple combination was 5%, encouragingly lower than those previously reported in the analysis of unrelated BMT through the Japan Marrow Donor Program, while the incidence of extensive chronic GVHD was apparently similar [27,35].…”
Section: Discussionmentioning
confidence: 98%
“…2 During mid-1990s when neighbouring countries started their allogeneic BMT programme, patients were referred to Singapore and Malaysia. [3][4][5][6][7][8][9][10] There was a hope at that time that allogeneic BMT would also be performed in Indonesia, that is, in Semarang and Jakarta but was later stopped after having been done in small number of patients.…”
Section: Transplantation (Allogeneic and Pbsc)mentioning
confidence: 99%